FACTORS AFFECTING THE PRODUCTIVITY OF FRUIT GROWING ON FARMS (ResearchJet Journal of Analysis and Inventions, 2021)
The article is based on data from farms specializing in horticulture. Factors affecting horticultural productivity relate to linear, mixed (combined), logarithmic and semi-logarithmic econometric models, optimally isolated and analyzed among the found models.